2013
DOI: 10.7763/ijmlc.2013.v3.316
|View full text |Cite
|
Sign up to set email alerts
|

Acquiring ICT Competencies Using Computer Based Learning

Abstract: Abstract-Studies have shown that the application of information and communication technology (ICT) in classrooms is still at an unsatisfactory level. The purposes of this research are to determine the skill of primary school teachers especially those teaching in rural areas in using IT, and thereafter to develop a multimedia learning package (WEDPI Package). The ICT aspect refers to productivity tools, which include applications for word-processing, electronic spreadsheet, database, presentation and the Intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In order to affect change in the era of digital education, government, businesses and industry need to work together to ensure the wider accessibility of digital education, including societal inclusion, so that every individual learner, has access to the opportunity for digital learning and the benefits which digital technology can offer in this sector [2]; Training programs and educational softwares have been developed to enhance the digital skills among students [15] as well as for teachers [16] and Collaboration, experiential learning and personal relevance found to support and foster the development of digital information literacy [17]. The studies also revealed that not only students [18,19,20,21] but also the teachers of primary level [22] and university faculty members [23] lack digital literacy, skills and digital competence required in the present digital era. Even the the level of digital competence among digital natives was found to be very low [24].…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…In order to affect change in the era of digital education, government, businesses and industry need to work together to ensure the wider accessibility of digital education, including societal inclusion, so that every individual learner, has access to the opportunity for digital learning and the benefits which digital technology can offer in this sector [2]; Training programs and educational softwares have been developed to enhance the digital skills among students [15] as well as for teachers [16] and Collaboration, experiential learning and personal relevance found to support and foster the development of digital information literacy [17]. The studies also revealed that not only students [18,19,20,21] but also the teachers of primary level [22] and university faculty members [23] lack digital literacy, skills and digital competence required in the present digital era. Even the the level of digital competence among digital natives was found to be very low [24].…”
Section: Review Of Related Literaturementioning
confidence: 99%